(3QSGdI aj GdaUOs - (3CMeO Hf eMeO CHh GdMSf GdWHQj, fMh (B360 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hdi GdMeO Efj QCjJ CWHGA LQLGf haUGOge jCJhf GdTF ef ZjQ JejjR hbO cfJ UfaJ ebGdI HGdQi , GdaUGOjf EfJaYhG HgG , hde jHb efge CMO EdG hGfJSNgG hMaXgG s
(3BNQgG (B:s
(3hjLH Cf jchf GdEfSGf Ydi MPQ ef Gf jbY Ydjg TF bO jfbHV Ch jfaJM KGfjkG, aEf ajg NWQkG YXjekG s
(3GfXQgG eY GdeQTOs
(3ddQGRj Qbe (B"730"s
(3fSNI KGfjI ecQQI Yf GdSGHbIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs